The classical Stefan problem basic concepts, modelling and analysis with quasi-analytical solutions and methods - Gupta, S. C. (Amsterdam, Netherlands Elsevier, 2018)
The Classical Stefan Problem: Basic Concepts, Modelling and Analysis with Quasi-Analytical Solutions and Methods, New Edition, provides fundamental theory, concepts, modelling and analysis of the physical, mathematical, thermodynamical and metallurgical properties of classical Stefan and Stefan-like problems as applied to heat transfer problems involving phase-changes, such as from liquid to solid. This self-contained work reports and derives the results from tensor analysis, differential geometry, non-equilibrium thermodynamics, physics and functional analysis, and is thoroughly enriched with many appropriate references for an in-depth background reading on theorems. This new edition includes more than 400 pages of new material on quasi-analytical solutions and methods of classical Stefan and Stefan-like problems. The book aims to bridge the gap between the theoretical and solution aspects of the afore-mentioned problems.--Provided by publisher.
Chapter 1 - The Stefan Problem and Its Classical Formulation -- Chapter 2 - Thermodynamical and Metallurgical Aspects of Stefan Problems -- Chapter 3 - Extended Classical Formulations of n-Phase Stefan Problems With n ≥ 1 -- Chapter 4 - Stefan Problem With Supercooling: Classical Formulation and Analysis -- Chapter 5 - Superheating due to Volumetric Heat Sources: The Formulation and Analysis -- Chapter 6 - Steady-State and Degenerate Classical Stefan Problems -- Chapter 7 - Elliptic and Parabolic Variational Inequalities -- Chapter 8 - The Hyperbolic Stefan Problem -- Chapter 9 - Inverse Stefan Problems -- Chapter 10 - Analysis of the Classical Solutions of Stefan Problems -- Chapter 11 - Regularity of the Weak Solutions of Some Stefan Problems -- Chapter 12 - Quasi-Analytical Solutions and Methods -- Appendix A - Preliminaries -- Appendix B - Some Function Spaces and Norms -- Appendix C - Fixed Point Theorems and Maximum Principles -- Appendix D - Sobolev Spaces -- Bibliography -- Index.
Includes bibliographical references (pages 683-716) and index.
Keywords: Heat -- Transmission; Boundary value problems; Electronic books